Copy number variations in candidate genomic regions confirm genetic heterogeneity and parental bias in Hirschsprung disease - Lantieri, Francesca; Gimelli, Stefania; Viaggi, Chiara; Stathaki, Elissavet; Malacarne, Michela; Santamaria, Giuseppe; Grossi, Alice; Mosconi, Manuela; Sloan-Béna, Frédérique; Prato, Alessio Pini; Coviello, Domenico; Ceccherini, Isabella (Orphanet journal of rare diseases, 2019)
Background Hirschsprung Disease (HSCR) is a congenital defect of the intestinal innervations characterized by complex inheritance. Many susceptibility genes including RET , the major HSCR gene, and several linked regions and associated loci have been shown to contribute to disease pathogenesis. Nonetheless, a proportion of patients still remains unexplained. Copy Number Variations (CNVs) have already been involved in HSCR, and for this reason we performed Comparative Genomic Hybridization (CGH), using a custom array with high density probes. Results A total of 20 HSCR candidate regions/genes was tested in 55 sporadic patients and four patients with already known chromosomal aberrations. Among 83 calls, 12 variants were experimentally validated, three of which involving the HSCR crucial genes SEMA3A/3D, NRG1, and PHOX2B. Conversely RET involvement in HSCR does not seem to rely on the presence of CNVs while, interestingly, several gains and losses did co-occur with another RET defect, thus confirming that more than one predisposing event is necessary for HSCR to develop. New loci were also shown to be involved, such as ALDH1A2, already found to play a major role in the enteric nervous system. Finally, all the inherited CNVs were of maternal origin. Conclusions Our results confirm a wide genetic heterogeneity in HSCR occurrence and support a role of candidate genes in expression regulation and cell signaling, thus contributing to depict further the molecular complexity of the genomic regions involved in the Enteric Nervous System development. The observed maternal transmission bias for HSCR associated CNVs supports the hypothesis that in females these variants might be more tolerated, requiring additional alterations to develop HSCR disease.